2021
DOI: 10.1038/s41598-021-97747-w
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, antioxidant properties of carotenoids and its optoelectronic and interaction studies with chlorophyll pigments

Abstract: The physicochemical and antioxidant properties of seven carotenoids: antheraxanthin, β-carotene, neoxanthin, peridinin, violaxanthin, xanthrophyll and zeaxanthin were studied by theoretical means. Then the Optoelectronic properties and interaction of chlorophyll-carotenoid complexes are analysed by TDDFT and IGMPLOT. Global reactivity descriptors for carotenoids and chlorophyll (Chla, Chlb) are calculated via conceptual density functional theory (CDFT). The higher HOMO–LUMO (HL) gap indicated structural stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 72 publications
0
15
0
8
Order By: Relevance
“…These results suggest that there is a direct relationship between the oscillator strength and the exciton diffusion, e.g., system 2 exhibits a significant hole population localized over the DHN fragment, which relates to an oscillator strength value larger than unity. This is a typical signature of the main energy absorption of carotenoid systems when their photophysical properties are studied with quantum mechanical methods. It is noteworthy that the more delocalized the exciton between the BChl- b fragments is, the larger their corresponding oscillator strength value, as it is noted for systems 4 , 6 , 7 , 9 , and 10 .…”
Section: Resultsmentioning
confidence: 93%
“…These results suggest that there is a direct relationship between the oscillator strength and the exciton diffusion, e.g., system 2 exhibits a significant hole population localized over the DHN fragment, which relates to an oscillator strength value larger than unity. This is a typical signature of the main energy absorption of carotenoid systems when their photophysical properties are studied with quantum mechanical methods. It is noteworthy that the more delocalized the exciton between the BChl- b fragments is, the larger their corresponding oscillator strength value, as it is noted for systems 4 , 6 , 7 , 9 , and 10 .…”
Section: Resultsmentioning
confidence: 93%
“…Previous research indicated that the pro-oxidation effect of carotenoids may be due to the imbalance in the cellular redox state, an excessive concentration of carotenoids, or an excessively high oxygen partial pressure [43]. Carotenoids are antioxidants that slow down or stop the chain of free radical reactions when oxygen saturation is low [44]. Nevertheless, when the oxygen concentration was high, carotenoid radicals were vulnerable to automatic oxidation by reacting with molecular oxygen while becoming aggressive carotenoid peroxy radicals, which promoted the lipid peroxidation and the oxidative damage of other biomolecules (such as DNA and proteins) [45].…”
Section: The Explanation Of Antioxidation and Pro-oxidation Effectsmentioning
confidence: 99%
“…Oxygen atoms are also present in the ring structure as hydroxyl or epoxide groups. Carotenoids typically have well-defined three-peaked absorption spectra, although epoxidation can change the absorption maxima depending on where double bonds are located in the ring [ 22 , 23 , 24 ].…”
Section: An Overview Of Microalgal Carotenoidsmentioning
confidence: 99%